Titanium-silicon compound catalyst, preparation method thereof and method for depolymerizing polyethylene glycol terephthalate
Through the use of titanium-silicon composite catalyst, the problems of heavy metal components and low efficiency of the depolymerization catalyst in the prior art have been solved, and efficient PET alcoholylation and high-purity recycled polyester production are achieved, which is suitable for closed-loop recycling of PET .
Patent Information
- Application Number
- CN202310836415.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-10
AI Technical Summary
In the prior art, the depolymerization catalyst contains heavy metal components, has low depolymerization efficiency, and high catalyst residue in the depolymerization product, resulting in the problem of low quality of regenerated polyester.
A titanium-silicon compound catalyst was developed, and a catalyst for alcoholylation PET was prepared by reacting the titanium compound with orthosilicate compounds and organic acid solutions, and depolymerization reaction was carried out under a protective atmosphere to obtain Highly efficient and highly selective alcoholylation products.
The PET depolymerization rate is >99.5%, the titanium residue in the target product is low, the product purity is high, and it is suitable for the closed-loop recycling of PET, and the catalyst is easy to remove from the depolymerization system, avoiding the occurrence of side reactions.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical degradation of waste polyester and relates to a titanium-silicon series composite catalyst and a preparation method thereof and a method for depolymerizing polyethylene terephthalate. Background Art
[0002] Polyethylene terephthalate (PET, referred to as polyester) is a semi-crystalline thermoplastic polymer material with excellent performance and low price. It is widely used in fiber, film, bottle and other fields. At present, the domestic PET production is about 60 million tons / year. The huge polyester market has led to an increasing amount of waste polyester. Polyester has stable chemical properties and is not enough to complete effective natural degradation within 16 to 48 years. It not only damages the ecological environment, but also wastes petroleum resources. Therefore, the effective use of waste resources and the recycling and reuse of waste polyester products are one of the key issues in achieving sustainable development in the polyester field.
[0003] The recycling methods of waste polyester are mainly divided into physical recycling and chemical recycling. Physical recycling refers to the recycling of waste polyester products, removing impurities, cleaning, crushing and drying, and then melting and granulating them for re-molding. The process is simple, with low investment and low cost. However, physical recycling can only be recycled at a downgraded level. At the same time, the recycled polyester contains a large amount of impurities, making it difficult to improve the quality. In addition, the number of recycling times is limited, and there is a problem of secondary pollution. Chemical recycling can achieve closed-loop recycling from "polymer-monomer-polymer" to obtain high-value multi-variety recycled products with good economic and social benefits.
[0004] Chemically recycled polyester is based on the reversibility of polycondensation reaction and the nucleophilic reaction mechanism of ester exchange. By depolymerizing waste polyester into monomers or polymerization intermediates, separating and purifying, high-purity monomers are obtained, and then polymerized into high-quality recycled polyester to achieve closed-loop recycling of waste polyester. Compared with other chemical regeneration methods, alcoholysis technology is relatively mature, while ethylene glycol alcoholysis has a simple reaction route, mild reaction conditions, low requirements for temperature and pressure, high safety factor, and can be used in conjunction with industrial PET polymerization equipment. It is suitable for industrial mass production, greatly improving economic benefits and reducing equipment maintenance costs. However, due to the reversible nature of polycondensation reaction, PET depolymerization and polymerization are a balanced reaction, and it is difficult to achieve an ideal depolymerization yield. There will be a certain amount of oligomer products in the depolymerization product, and the separation and purification process of the product is difficult, and the purity and yield of the target product are not high. Currently, the depolymerization catalysts commonly used in industry are metal salts represented by zinc acetate, which will remain in the target product after depolymerization and are difficult to remove. High levels of catalyst residues will lead to serious thermal degradation side reactions of the regenerated product, affecting the quality of the regenerated polyester.
[0005] The mechanism of action of titanium catalysts is similar to that of commonly used metal catalysts. In the alcoholysis of polyester, the titanium ions on the titanium catalysts will first attack the carbonyl carbon on the polyester due to their low potential, form a complex through coordination bonds, redistribute the charge, reduce the charge of the carbonyl carbon, and are easily attacked by the hydroxyl oxygen on the ethylene glycol, thereby initiating the breakage of the ester bond in the PET molecule to generate alcoholysis products. Compared with other catalysts, titanium catalysts have higher selectivity and catalytic activity, and their residues have no obvious harm to the environment and human body. They are efficient and green environmentally friendly catalysts; however, since they are a commonly used polymerization catalyst for polyester, excessive titanium catalyst residues will lead to serious side reactions, reduced product performance and poor color. By introducing a certain amount of silicon atoms into the titanium active center, not only can the catalytic activity of titanium be effectively adjusted and the amount of titanium used in the reaction system be reduced, but the residual amount of titanium in the target monomer can also be significantly reduced, thereby avoiding affecting the regeneration of the target monomer.
[0006] Therefore, in order to solve the above problems, the present invention provides a catalyst and a method for alcoholysis of waste polyester with high efficiency. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art that the depolymerization catalyst contains heavy metal components, the depolymerization efficiency is low, the catalyst residue in the depolymerization product is high, and the quality of the regenerated polyester is low. A titanium-silicon composite catalyst that can be used for the alcoholysis of polyethylene terephthalate (PET) and a preparation method thereof are provided, and a method for depolymerizing polyethylene terephthalate using the catalyst is provided.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a titanium-silicon composite catalyst, the method comprising:
[0009] (1) preparing a titanium compound, an orthosilicate compound and a solvent and reacting them with an organic acid solution to obtain a solution;
[0010] (2) Post-treating the solution to obtain a titanium-silicon composite catalyst.
[0011] The second aspect of the present invention provides a titanium-silicon composite catalyst prepared by the first aspect of the present invention.
[0012] A third aspect of the present invention provides a method for depolymerizing polyethylene terephthalate (PET),
[0013] The method includes:
[0014] In the presence of a catalyst and a protective atmosphere, the treated polyethylene terephthalate-containing material and alcohol are subjected to a depolymerization reaction to obtain an alcoholysis product containing bis(2-hydroxyethyl) terephthalate (BHET);
[0015] Wherein, the catalyst is the titanium-silicon composite catalyst prepared according to the first aspect of the present invention.
[0016] Through the above technical solution, the present invention achieves the following beneficial effects:
[0017] (1) The titanium-silicon composite catalyst for alcoholysis of PET developed by the present invention has high efficiency and high selectivity, low addition amount, PET depolymerization rate>99.5%, after depolymerization, the polymerization degree in the depolymerization product is only 1-3, the total content of BHET monomer, BHET dimer, and BHET trimer is>99wt%, and the BHET monomer content is>93wt%.
[0018] (2) The high-efficiency titanium-silicon composite catalyst developed by the present invention does not contain heavy metals and is harmless to the environment and human body. The target product BHET has a low titanium residue content and has little effect on PET regeneration.
[0019] (3) The BHET obtained by the method of the present invention can be directly used to prepare PET or other high value-added products, thereby realizing the closed-loop recycling of PET.
[0020] (4) The titanium-silicon composite catalyst developed by the present invention uses titanium as the main catalyst body, with a content of 10-50wt%; the pH value of the titanium-silicon composite catalyst is 2-5, and the infrared spectrum of the catalyst is at 1022cm -1 There is an absorption peak at . In order to make it easy to remove the catalyst from the depolymerization system, the titanium-silicon composite catalyst is a heterogeneous system. The catalyst activity remains unchanged after boiling in ethylene glycol at high temperature for 4 hours, and the catalyst does not undergo alcoholysis reaction in the high-temperature alcoholysis polyester reaction. In addition, by introducing silicon atoms into the titanium active center, the catalytic activity of titanium can be effectively adjusted; the use of hydroxycarboxylic acid compounds such as citric acid and lactic acid can form a relatively stable structure with titanate, and can depolymerize most of the waste plastics with a waste polyester PET content of ≥75%, and the catalyst activity is stable. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The first aspect of the present invention provides a method for preparing a titanium-silicon composite catalyst, the method comprising:
[0023] (1) preparing a titanium compound, an orthosilicate compound and a solvent and reacting them with an organic acid solution to obtain a solution;
[0024] (2) Post-treating the solution to obtain a titanium-silicon composite catalyst.
[0025] In one embodiment of the present invention, preferably, the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, tetraethyl titanate, titanium glycolate, titanium acetylacetonate, and diisopropyl di(acetylacetonate) titanate.
[0026] In one embodiment of the present invention, preferably, the orthosilicate is selected from tetrabutyl orthosilicate, tetraethyl orthosilicate, and tetramethyl orthosilicate.
[0027] In one embodiment of the present invention, preferably, the organic acid in the organic acid solution is selected from one or more of citric acid, malic acid, salicylic acid, tartaric acid and lactic acid.
[0028] In one embodiment of the present invention, preferably, the solvent is selected from one or more of ethanol, isopropanol and water.
[0029] In one embodiment of the present invention, preferably, the molar ratio of the titanium compound to the orthosilicate compound is 95:5-70:30.
[0030] In one embodiment of the present invention, preferably, the molar ratio of the titanium compound to the organic acid in the organic acid solution is 1:8-1:0.5.
[0031] In one embodiment of the present invention, preferably, the molar ratio of the titanium compound to the solvent is 1:1-1:50.
[0032] In one embodiment of the present invention, preferably, the preparation temperature is 20-40°C.
[0033] In one embodiment of the present invention, preferably, during the preparation process in step (1), the stirring time is 2-3 hours.
[0034] In one embodiment of the present invention, preferably, the mass ratio of the organic acid to the dissolving solvent contained in the organic acid solution in step (1) is 1:3-10; at a temperature of 30-70°C and a stirring speed of 10-30r / min, the organic acid is completely dissolved in the dissolving solvent and then transferred into a burette.
[0035] In one embodiment of the present invention, preferably, the reaction process comprises: adding the organic acid solution in the burette to a mixture of the titanium compound, the orthosilicate compound and the solvent at a dropping speed of 1 mL / min, and after the dropping is completed, reacting at 20-40°C for 2-3 hours.
[0036] In one embodiment of the present invention, preferably, the post-treatment process in step (2) comprises:
[0037] (i) The solution is heated to distill out small molecules.
[0038] (ii) After the small molecules are no longer distilled out, the material is cooled and discharged to obtain a titanium-silicon composite catalyst.
[0039] In one embodiment of the present invention, preferably, during the post-treatment in step (i), the solution is heated to 100-150°C.
[0040] In one embodiment of the present invention, preferably, the temperature after cooling in step (ii) is room temperature, and the discharging is to place the product obtained after cooling in a vacuum drying oven and dry it for 1-3 hours.
[0041] The second aspect of the present invention provides a titanium-silicon composite catalyst prepared by the first aspect of the present invention.
[0042] In one embodiment of the present invention, preferably, in the titanium-silicon composite catalyst, the content of titanium is 10-50wt%, and the content of silicon is 0.3-9.5wt%.
[0043] In one embodiment of the present invention, preferably, the pH value of the titanium-silicon composite catalyst is 2-5.
[0044] In one embodiment of the present invention, preferably, the infrared spectrum of the titanium-silicon composite catalyst is at 1022 cm -1 There is an absorption peak at. The titanium-silicon composite catalyst prepared by the present invention may contain substances formed by the preparation method of the first aspect, which is reflected in the infrared spectrum. The titanium-silicon composite catalyst of the present invention can have a better effect of depolymerizing polyethylene terephthalate.
[0045] A third aspect of the present invention provides a method for depolymerizing polyethylene terephthalate (PET), the method comprising:
[0046] In the presence of a catalyst and a protective atmosphere, the treated polyethylene terephthalate (PET)-containing material and alcohol are subjected to a depolymerization reaction to obtain an alcoholysis product containing bis(2-hydroxyethyl) terephthalate;
[0047] Wherein, the catalyst is selected from the titanium-silicon composite catalyst prepared in the first aspect of the present invention.
[0048] In one embodiment of the present invention, preferably, the alcohol is a diol, preferably at least one or more selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.
[0049] In one embodiment of the present invention, preferably, the mass ratio of the polyethylene terephthalate to the alcohol is 1:2-1:8, preferably 1:3-1:5. If the amount of the alcohol added is too small, exceeding the above range, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0050] In one embodiment of the present invention, preferably, the amount of the catalyst is 0.05-0.5wt% of the polyethylene terephthalate, preferably 0.1-0.4wt%. If the amount of the rare earth composite catalyst added is too large, the amount of the catalyst residue in the final product BHET will increase, affecting the regeneration of the catalyst.
[0051] In the present invention, the amount of polyethylene terephthalate is based on the polyethylene terephthalate contained in the polyethylene terephthalate (PET)-containing material.
[0052] In the present invention, the "treatment" in the "treated polyethylene terephthalate (PET)-containing material" means cleaning the polyethylene terephthalate (PET)-containing material to remove oil, dust, non-PET and other impurities. In addition, the polyethylene terephthalate-containing material can be waste PET bottle flakes, waste PET long fibers, waste PET short fibers, waste polyester foam materials, waste PET films or materials with a PET content of ≥75wt%.
[0053] In one embodiment of the present invention, preferably, the reaction temperature of the depolymerization reaction is 190-250° C., preferably 200-230° C. If the reaction temperature is too low, the depolymerization reaction will be incomplete, the oligomers will increase, and the yield of the final product BHET will be affected.
[0054] In one embodiment of the present invention, preferably, the reaction pressure of the depolymerization reaction is 0.2-0.6 MPa, preferably 0.35-0.5 MPa. If the reaction pressure is too low, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0055] In one embodiment of the present invention, preferably, the reaction time of the depolymerization reaction is 1-5 hours, preferably 2-4 hours. If the reaction time is too short, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0056] The present invention will be described in detail below through examples.
[0057] In the following examples, the depolymerization rate of polyethylene terephthalate is shown in (Formula 1), and the yield of the product BHET is shown in (Formula 2), wherein the molecular weight of BHET is 254 g / mol, and the molecular weight of the repeating unit in PET is 192 g / mol.
[0058]
[0059]
[0060] Example 1
[0061] Isopropyl titanate (37.5 g) and butyl orthosilicate (9.2 g) were added into a reactor, and 80 mL of isopropanol was added. After stirring at 30°C for 1 hour, citric acid (16 g) was dissolved in 80 mL of isopropanol and slowly added dropwise into the reactants. The temperature was raised to 50°C and the reaction was carried out for 2 hours. The reactants were rotary evaporated at 70°C until the evaporation rate of small molecules slowed down significantly, and then dried in a vacuum drying oven at 70°C for 2 hours to obtain a titanium-silicon composite catalyst A.
[0062] Example 2
[0063] n-Butyl titanate (22.4 g) and ethyl orthosilicate (10.3 g) were added into a reactor, and 60 mL of ethanol was added. After stirring at 25°C for 1 hour, tartaric acid (23 g) was dissolved in 70 mL of ethanol and slowly added dropwise into the reactants. The temperature was raised to 40°C and the reaction was carried out for 3 hours. The reactants were rotary evaporated at 60°C until the evaporation rate of small molecules slowed down significantly, and then dried in a vacuum drying oven at 65°C for 4 hours to obtain a titanium-silicon composite catalyst B.
[0064] Example 3
[0065] Diisopropyl di(acetylacetonate)titanate (53.9 g) and tetraethyl orthosilicate (3.1 g) were added into a reactor, and then 50 mL of ethanol and 30 mL of isopropanol were added. After stirring at 35°C for 1.5 hours, salicylic acid (27.6 g) was dissolved in 80 mL of ethanol and slowly added dropwise into the reactants. The temperature was raised to 55°C and the reaction was carried out for 5 hours. The reactants were rotary evaporated at 70°C until the evaporation rate of small molecules slowed down significantly, and then dried in a vacuum drying oven at 70°C for 2 hours to obtain a titanium-silicon composite catalyst C.
[0066] Example 4
[0067] This example is used to illustrate the depolymerization of PET.
[0068] The treated waste PET bottle flakes and ethylene glycol were added to the reactor in a mass ratio of 1:4.5, and 0.3wt% (based on the mass of PET) of a homemade titanium-silicon composite catalyst A was added. The air in the reactor was replaced with nitrogen. After ensuring the air tightness of the reactor, a certain amount of nitrogen was introduced to make the pressure in the reactor reach 0.4MPa. The stirring was turned on, the temperature in the reactor was set to 200°C, and the timing was started after the reactor temperature rose to the set temperature. The reaction time was 3 hours, and a depolymerization product was obtained, and the PET depolymerization rate was 100%.
[0069] The depolymerization product was filtered while hot at 120°C to obtain a filtrate, deionized water was added at a ratio of filtrate: water = 1:3, and the mixture was stirred in a water bath at 80°C for 2 hours, and then filtered to obtain a filtrate. The filtrate was crystallized at room temperature for 8 hours, and then cooled and crystallized at 0-5°C for 2 hours. Crystal BHET was obtained by suction filtration, and dried in a drying oven at 70°C for 8 hours and then weighed to obtain the target monomer BHET with a purity of 97.1%.
[0070] Based on this embodiment, it can be seen that the titanium-silicon composite catalyst of the present invention has high efficiency and high selectivity in the alcoholysis of PET reaction. The total content of products with a degree of polymerization of oligomers of 1-3 in the alcoholysis product is 99.2%, and BHET accounts for 93.7% of the depolymerization product. After separation and purification, the residual titanium content in the target monomer is 81 mg / kg.
[0071] Example 5
[0072] The method of Example 4 is followed, except that the catalyst is a titanium-silicon composite catalyst B.
[0073] In Example 5, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 99.1%, BHET accounts for 93.5% of the depolymerization product, and after separation and purification, the purity of BHET is 97.0%, and the residual titanium content in the target monomer is 58 mg / kg.
[0074] Example 6
[0075] The method of Example 4 was followed, except that PET and ethylene glycol were added to the reactor at a mass ratio of 1:4.5, the catalyst was titanium-silicon composite catalyst C, and the depolymerization time was 2 hours.
[0076] In Example 6, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 99.2wt%, BHET accounts for 93.6wt% in the depolymerization product, and after separation and purification, the purity of BHET is 97.8wt%, and the residual titanium content in the target monomer is 47mg / kg.
[0077] Example 7
[0078] The method of Example 5 was followed, except that the amount of catalyst used was 0.2 wt % and the depolymerization temperature was 210°C.
[0079] In Example 7, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 99.0%, BHET accounts for 93.0% of the depolymerization product, and after separation and purification, the purity of BHET is 97.2%, and the residual titanium content in the target monomer is 34 mg / kg.
[0080] Example 8
[0081] The method of Example 6 was followed, except that the amount of catalyst used was 0.1 wt % and the depolymerization pressure was 0.3 MPa.
[0082] In Example 8, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 98.2%, BHET accounts for 90.5% of the depolymerization product, and after separation and purification, the purity of BHET is 96.9%, and the residual titanium content in BHET in the target monomer is 25 mg / kg.
[0083] Example 9
[0084] The method of Example 4 was followed, except that PET and ethylene glycol were added to the reactor at a mass ratio of 1:5, the amount of catalyst was 0.4 wt %, and the depolymerization reaction temperature was 190° C.
[0085] In Example 9, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 99.0%, BHET accounts for 94.5% of the depolymerization product, and after separation and purification, the purity of BHET is 97.3%, and the residual titanium content in the target monomer is 93 mg / kg.
[0086] Example 10
[0087] The method of Example 4 was followed, except that PET and ethylene glycol were added to the reactor in a mass ratio of 1:3, and the amount of catalyst was 0.2 wt%.
[0088] In Example 10, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 98.8%, BHET accounts for 93.9% of the depolymerization product, and after separation and purification, the purity of BHET is 97.0%, and the residual titanium content in the target monomer is 57 mg / kg.
[0089] Embodiment 11
[0090] The method of Example 8 was followed, except that PET and ethylene glycol were added to the reactor at a mass ratio of 1:2, the reaction pressure was 0.35 MPa, and the reaction time was 4 hours.
[0091] In Example 11, the PET depolymerization rate is 100%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis product is 98.0%, BHET accounts for 90.0% of the depolymerization product, and after separation and purification, the purity of BHET is 96.2%, and the residual titanium content in the target monomer is 89 mg / kg.
[0092] Example 12
[0093] The method of Example 8 is followed, except that the waste PET bottle flakes are replaced with waste polyester foam material, and the PET content is 93wt%.
[0094] In Example 12, the PET depolymerization rate is 99%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis products is 99.5%, BHET accounts for 91.3% of the depolymerization products, and after separation and purification, the purity of BHET is 98.0%, and the residual titanium content in the target monomer is 23 mg / kg.
[0095] Example 13
[0096] The method of Example 8 is followed, except that the waste PET bottle flakes are replaced with a waste plastic having a PET content of 78.5%.
[0097] In Example 13, the PET depolymerization rate was 99%, the total content of oligomers with a degree of polymerization of 1-3 in the alcoholysis products was 98.0%, BHET accounted for 99.1% of the depolymerization products, and after separation and purification, the purity of BHET was 98.40%, and the residual titanium content in the target monomer was 22 mg / kg.
[0098] Embodiment 14
[0099] Add 83 g of homemade BHET monomer and 0.52 g of tetrabutyl titanate into a three-necked flask, gradually heat up to 190°C under a nitrogen atmosphere, react for 1 hour, change to a vacuum distillation device, heat up to 280°C, gradually adjust the vacuum degree of the system to less than 300 Pa, and after reacting for 2.5 hours, obtain a PET product with a number average molecular mass of 19,000 g / mol.
[0100] Comparative Example 1
[0101] The treated waste PET bottle flakes and ethylene glycol are added to a reactor in a mass ratio of 1:4.5, and 0.3wt% (based on the mass of PET) of tetrabutyl titanate is added. The depolymerization pressure is 0.4MPa, the depolymerization temperature is 200°C, and the depolymerization time is 3 hours to obtain a depolymerization product. The PET depolymerization rate is 100%, the total content of products with a degree of polymerization of oligomers of 1-3 in the alcoholysis product is 97.6%, and BHET accounts for 91.7% of the depolymerization product. After separation and purification, the purity of BHET is 96.6%, and the titanium residue in the target monomer is 258mg / kg.
[0102] The experimental results of Examples 4-11 and Comparative Example 1 are summarized in Table 1.
[0103] Table 1
[0104]
[0105] Table 1
[0106]
[0107]
[0108] Table 1
[0109]
[0110] From the results in Table 1, it can be seen that Examples 4-11 using the technical solution of the present invention have significantly better effects than Comparative Example 1 in terms of the residual titanium content in the target monomer and the total amount of products with a degree of polymerization of oligomers of 1-3, Examples 4-10 have significantly better effects in terms of BHET purity, and Examples 4-7, 9 and 10 have significantly better effects in terms of the proportion of BHET in the depolymerization products. The results of Examples 12 and 13 also prove that the method of the present invention can be applied to the depolymerization process of other polyethylene terephthalate-containing materials other than waste PET bottle flakes. The results of Example 14 prove that the BHET obtained by the method of the present invention can be directly used to prepare PET polyester products or other high value-added products, realizing the closed-loop recycling of PET.
[0111] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a titanium-silicon composite catalyst, the method comprising: (1) preparing a titanium compound, an orthosilicate compound and a solvent and reacting them with an organic acid solution to obtain a solution; (2) Post-treating the solution to obtain a titanium-silicon composite catalyst.
2. The preparation method according to claim 1, wherein The titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, tetraethyl titanate, titanium glycolate, titanium acetylacetonate, and diisopropyl di(acetylacetonate) titanate.
3. The preparation method according to claim 1 or 2, wherein The orthosilicate compound is selected from one or more of tetrabutyl orthosilicate, tetraethyl orthosilicate and tetramethyl orthosilicate.
4. The preparation method according to any one of claims 1 to 3, wherein The organic acid in the organic acid solution is selected from one or more of citric acid, malic acid, salicylic acid, tartaric acid and lactic acid.
5. The preparation method according to any one of claims 1 to 4, wherein: The solvent is selected from one or more of ethanol, isopropanol and water.
6. The method according to any one of claims 1 to 5, wherein: The molar ratio of the titanium compound to the orthosilicate compound is 95:5-70:30; Preferably, the molar ratio of the titanium compound to the organic acid in the organic acid solution is 1:8-1:0.5; Preferably, the molar ratio of the titanium compound to the solvent is 1:1-1:
50.
7. The preparation method according to any one of claims 1 to 6, wherein: The reaction temperature in step (1) is 20-40°C.
8. The preparation method according to any one of claims 1 to 7, wherein: The reaction time in step (1) is 2-3 hours.
9. A titanium-silicon composite catalyst prepared by the method according to any one of claims 1 to 8; Preferably, in the titanium-silicon composite catalyst, the content of titanium is 10-50wt%, and the content of silicon is 0.3-9.5wt%; Preferably, the pH value of the titanium-silicon composite catalyst is 2-5; Preferably, the infrared spectrum of the titanium-silicon composite catalyst is at 1022 cm -1 There is an absorption peak.
10. A method for depolymerizing polyethylene terephthalate, the method comprising: In the presence of a catalyst and a protective atmosphere, the treated polyethylene terephthalate-containing material and alcohol are subjected to a depolymerization reaction to obtain an alcoholysis product containing bis(2-hydroxyethyl) terephthalate; Wherein, the catalyst is the titanium-silicon composite catalyst as described in claim 9.
11. The method according to claim 10, wherein: The alcohol is a diol, and is preferably selected from at least one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.
12. The method according to claim 10 or 11, wherein: The mass ratio of the polyethylene terephthalate to the alcohol is 1:2-1:8, preferably 1:3-1:
5.
13. The method according to any one of claims 10 to 12, wherein: The amount of the catalyst used is 0.05-0.5 wt % of the polyethylene terephthalate, preferably 0.1-0.4 wt %.
14. The method according to any one of claims 10 to 13, wherein: The reaction temperature of the depolymerization reaction is 190-250°C, preferably 200-230°C.
15. The method according to any one of claims 10 to 14, wherein: The reaction pressure of the depolymerization reaction is 0.2-0.6 MPa, preferably 0.35-0.5 MPa.
16. The method according to any one of claims 10 to 15, wherein: The reaction time of the depolymerization reaction is 1-5 h, preferably 2-4 h.
Citation Information
Patent Citations
Process for preparing liquid condition titanium catalyst for preparing polyester and copolyester
CN101270185A
Liquid titanium catalyst for polyester and copolyester and preparation method thereof
CN102382287A
Liquid titanium catalyst and preparation method for producing polyester polymer by using same
CN106084189A
Catalyst and process
US20060155102A1
Liquid Titanium-Based Catalyst And Method For Preparing Polyester Polymer Thereof
US20170121455A1
Cited By
Recycling method of solar back plate
CN120248420A
Method for improving yield and purity of regenerated BHET
CN121758280A
Catalyst for degrading PET (Polyethylene Terephthalate), degradation method, preparation method and recovery method
CN121775917A
Bis (2-hydroxyethyl) terephthalate and polybutylene terephthalate as well as preparation method and application of bis (2-hydroxyethyl) terephthalate and polybutylene terephthalate
CN122102895A
Fat aromatic copolyester as well as preparation method and application thereof
CN122103533A